The perception of the barbarian in the “time of kingdoms”: infidelity, betrayal and violence in the Hispano-Visigothic kingdom of Toledo (6th – 7th centuries) - Frighetto, Renan (Romanitas - Revista de Estudos Grecolatinos, 2026)
Late Antiquity (3rd–8th centuries) is considered a dynamic historical framework, replete with transformations, readjustments, and mutations. As part of this context, we find the characterization of the barbarian, which underwent significant changes. From a Greco-Roman civilizational perspective concerned with the threats posed by culturally and politically distinct population groups, we observe that the interaction and integration of those considered barbarians into the sociopolitical and cultural environment of western Roman territories from the 5th century onwards ultimately transformed the notion of the barbarian, which, from then on, integrated itself into aristocratic groups of Roman and indigenous origin. So much so that the Goths, who formed a regnum in the territory of ancient Roman Hispania between the 6th and 7th centuries, used tools traditionally associated with the Roman imperial tradition to configure a new barbarian profile with a political-ideological accent, where infidelity, betrayal, and religious issues began to play a significant role.